THE EFFECT of E-GLASS FIBERS and ACRYLIC RESIN THICKNESS on FRACTURE LOAD IN A SIMULATED IMPLANT-SUPPORTED OVERDENTURE PROSTHESIS - Fajardo, Renato Salviato [UNESP]; Pruitt, Lisa A.; Finzen, Frederick C.; Marshall, Grayson W.; Singh, Sukhmony; Curtis, Donald A. (Mosby-elsevier, 2011)
Statement of problem. Implant overdenture prostheses are prone to acrylic resin fracture because of space limitations around the implant overdenture components.Purpose. The purpose of this study was to evaluate the influence of E-glass fibers and acrylic resin thickness in resisting acrylic resin fracture around a simulated overdenture abutment.Material and methods. A model was developed to simulate the clinical situation of an implant overdenture abutment with varying acrylic resin thickness (1.5 or 3.0 mm) with or without E-glass fiber reinforcement. Forty-eight specimens with an underlying simulated abutment were divided into 4 groups (n=12): 1.5 mm acrylic resin without E-glass fibers identified as thin with no E-glass fiber mesh (TN-N); 1.5 mm acrylic resin with E-glass fibers identified as thin with E-glass fiber mesh (TN-F); 3.0 mm acrylic resin without E-glass fibers identified as thick without E-glass fiber mesh (TK-N); and 3.0 mm acrylic resin with E-glass fibers identified as thick with E-glass fiber mesh (TK-F). All specimens were submitted to a 3-point bending test and fracture loads (N) were analyzed with a 2-way ANOVA and Tukey's post hoc test (alpha=.05).Results. The results revealed significant differences in fracture load among the 4 groups, with significant effects from both thickness (P<.001) and inclusion of the mesh (P<.001). Results demonstrated no interaction between mesh and thickness (P=.690). The TN-N: 39 +/- 5 N; TN-F: 50 +/- 6.9 N; TK-N: 162 +/- 13 N; and TK-F: 193 +/- 21 N groups were all statistically different (P<.001).Conclusions. The fracture load of a processed, acrylic resin implant-supported overdenture can be significantly increased by the addition of E-glass fibers even when using thin acrylic resin sections. on a relative basis, the increase in fracture load was similar when adding E-glass fibers or increasing acrylic resin thickness. (J Prosthet Dent 2011;106:373-377)